2003
DOI: 10.1093/pcp/pcg017
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Expression of a Novel-Type Ammonium Transporter OsAMT2 in Rice Plants

Abstract: ;To characterize ammonium transport pathways in rice, two cDNAs with high homology to MEP/AMT2-type ammonium transporters, OsAMT2;1 and OsAMT3;1, were isolated. Expression of OsAMT2;1 in an ammoniumuptake-defective yeast mutant showed that this gene encodes functional ammonium transporters. OsAMT2;1 was constitutively expressed in both roots and shoots irrespective of the supply of inorganic nitrogen to the medium, whereas OsAMT3;1 expression was relatively weak. A database search with the amino acid sequence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
107
0
7

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(120 citation statements)
references
References 23 publications
(31 reference statements)
6
107
0
7
Order By: Relevance
“…From this point of view, LjAMT2;2, with its two introns, fits well into the AMT2 subfamily. This picture is also confirmed by the phylogenetic analysis that placed LjAMT2;2 in the AMT2 subgroup 4 (Suenaga et al, 2003) of O. sativa and P. trichocarpa (Couturier et al, 2007). Interestingly, transcripts from this subgroup are rare or not detected at all in several species (Suenaga et al, 2003;Couturier et al, 2007).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…From this point of view, LjAMT2;2, with its two introns, fits well into the AMT2 subfamily. This picture is also confirmed by the phylogenetic analysis that placed LjAMT2;2 in the AMT2 subgroup 4 (Suenaga et al, 2003) of O. sativa and P. trichocarpa (Couturier et al, 2007). Interestingly, transcripts from this subgroup are rare or not detected at all in several species (Suenaga et al, 2003;Couturier et al, 2007).…”
Section: Discussionsupporting
confidence: 57%
“…This picture is also confirmed by the phylogenetic analysis that placed LjAMT2;2 in the AMT2 subgroup 4 (Suenaga et al, 2003) of O. sativa and P. trichocarpa (Couturier et al, 2007). Interestingly, transcripts from this subgroup are rare or not detected at all in several species (Suenaga et al, 2003;Couturier et al, 2007). EST sequences have so far only been reported for two members: PtrAMT4;2 in floral buds and PtrAMT4;5 in poplar cultured cells (Couturier et al, 2007).…”
Section: Discussionmentioning
confidence: 58%
“…Members of the AMT1 and AMT2 subfamilies differ in their biochemical and sequence characteristics with the latter being more closely related to bacterial AMT transporters (Sohlenkamp et al 2000). Genome sequencing has revealed three AMT1 genes in Oriza sativa , five in Arabidopsis thaliana and eight in Populus trichocarpa (Couturier et al 2007); whereas one, six and seven AMT2 genes were identified in A. thaliana (Sohlenkamp et al 2000) P. trichocarpa (Couturier et al 2007) and O. sativa (Suenaga et al 2003), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…AMT1 gene family was first identified from Saccharomyces and Arabidopsis (Gazzarrini et al 1999), subsequently cloned from Oryza sativa (Suenaga et al 2003), Medicago truncatula (Straub et al 2014), Lotus japonicas (Salvemini et al 2001), Brassica napus (Pearson et al 2002), Lycopersicon esculentum (von Wiren et al 2000), Populus trichocarpa (Couturier et al 2007), Sorghum bicolor (Koegel et al 2013) etc. Among woody plants constitutive organ-specific AMT1 transcription was detected only in Populus (Couturier et al 2007), Citrus (Camanes et al 2007) and Pyrus (Li et al 2015).…”
Section: Introductionmentioning
confidence: 99%